E-business as a tool for the improvement of commercial management in industrial companies of Buenaventura - Quintero Paz, Cintia
Although it is known that companies today have much more capacity for adaptation, 2020 devastated the labor market, a difficult year for the vast majority of companies in the world because they experienced a considerable drop in their income, both due to changes in consumption patterns as well as the sanitary restrictions implemented by governments. For this reason; The SENNOVA program and its Human Entrepreneurship research hotbed of the Nautical Fishing Center carried out this research work in order to contribute to the participation in the markets of SMEs in the industrial sector of Buenaventura.The companies object of the study were SMEs established in Buenaventura, belonging to the industrial sector, 434 registered companies complied with the profiling of the project. According to sample calculation, 26 SMEs were selected, collecting information through field work, applying an information collection instrument, allowing to know the current situation of SMEs registered in the Chamber of Commerce and identifying needs that impeded their growth. Once the information was collected, the analysis and decision-making process was carried out, as a result, 6 companies in the sector with low market participation were evidenced to intervene. Having identified the needs in each of the organizations, an E-business tool was acquired to generate optimization and efficiency in the processes that were carried out in them; This process was accompanied by a digital marketing specialist to display them in the market and attract a much wider audience. Allowing each of them today to have their social networks (Facebook, Instagram), a website compatible with computers and mobiles, advertising pieces, Chat Bots connected to WhatsApp to serve their customers 24/7, automating the responses required by their public